(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes the economic and geographical factors affecting the formation of the infrastructure of secondary schools in the Kashkadarya region. The study studies the location of schools, their material and technical base, population density and the level of socio-economic development based on a geographical approach. In particular, the imbalances in the educational infrastructure in mountainous and remote areas, transport and communication problems, and the need for new schools are scientifically covered. The article reveals regional differences based on statistical and cartographic materials and gives practical recommendations for planning and developing educational institutions taking into account economic and geographical conditions. The results of the study are important in developing regional education policy and determining a strategy for developing school infrastructure.